KUALITAS PERIJINAN BERBASIS OSS (OPEN SINGLE SUBMISSION) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SAMARINDA - Dody Kusuma Prayuda; Abdur Rahman; Gusti Naufal Rizky; Andi Muhammad Rifqi (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
Adaptive governance is a concept of governance that adapts to conditions of uncertainty and environmental change so that it is relevant and effective for long-term goals. The purpose of this study is to describe and analyze Online Single Submisson (OSS) licensing services at the Investment and One-Stop Integrated Service Office (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu or DPMPTSP – in Indonesian) in Samarinda City that adapt to respond to the development of the business climate in Samarinda City and to identify the inhibiting factors. Data collection was carried out by observation, interview and documentation methods. The results of the study show that the quality of the OSS licensing service at DPMPTSP Samarinda City is more efficient with regard to the administrative process of costs and labor and no paper is used in terms of fulfillment cannot fulfill the promise of integrated. For the availability of the system, there not yet available access in the form application on smartphone. The inhibiting factor in its implementation comes from business actors who do not fully meet the basic requirements of the four commitments.